The Impact of Fiscal Policies on Economic Diversification in Saudi Arabia: An Analytical Study for the Period (2000 – 2020) - Almutairi, Othman Hezam (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of the fiscal policies taken by Saudi government to achieve economic diversification during the period from 2000 to 2020. The study used the descriptive analytical method relying on secondary data such as research, studies, reports, and statistics from official authorities inside and outside Saudi Arabia. After reviewing Saudi development plans from (2000 to 2020) and the economic diversification objectives included in these plans, many fiscal policies were taken by Saudi government to achieve economic diversification objectives. The study used Hervendal-Hirschman Index HHI to measure the impact of fiscal policies on the level of economic diversification in Saudi Arabia’ economy. The study found that the impact of fiscal policy was limited during the period from 2000 to 2015. However, the HHI showed a remarkable improvement in the level of diversification started from 2016 to 2020 which can be attributed to the following reasons: rationalizing operational spending and focusing on investment spending to enhance the role of the private sector, support small and medium businesses, and enhancing government sources of income through imposing value-added tax VAT, selective goods tax SGT and expatriate fees.
Keywords: Fiscal Policy; Economic Diversification; Government Spending; Sustainable Development